The existence of solutions for the modified (p(x), q(x))-Kirchhoff equation - Figueiredo Giovany M.; Vetro Calogero (2022)
We consider the Dirichlet problem Kp p(x) u(x) − ∆ Kq q(x) u(x) = f(x, u(x), ∇u(x)) in Ω, u = 0, driven by the sum of a p(x)-Laplacian operator and of a q(x)-Laplacian operator, both of them weighted by indefinite (sign-changing) Kirchhoff type terms. We establish the existence of weak solution and strong generalized solution, using topological tools (properties of Galerkin basis and of Nemitsky map). In the particular case of a positive Kirchhoff term, we obtain the existence of weak solution (= strong generalized solution), using the properties of pseudomonotone operators.
Keywords: Természettudományok; Matematika